The determinants of regional growth: An empirical analysis - Stefano Magrini (European Regional Science Association (ERSA), 1998)
The paper analyses the growth process at work in the European Union during the period 1979-1990. The first part of the paper describes a theoretical model that guides the empirical work. Particular emphasis is placed on the role played by human capital, research activities and spillovers of technological knowledge. The model is then tested using OLS on a database of 122 major European Functional Urban Regions (FURs)
Keywords: 330